Competitive Advantage Analysis in Pharmacy Companies - Margarita Išoraitė (Integrated Journal of Business and Economics (IJBE), 2019)
Article analyzes competitive advantage theoretical aspects and also competitive advantage in pharmacy sector in Lithuania. Competitive advantage is what all (competing) business strategies are directed to. Many factors can provide a competitive advantage; it can be more efficient production, available patents, good advertising, good management, and good customer relations.